Cobre e zinco em dejeto líquido de suíno com adição de pó-de-metabasalto - Perdoncini, Daiana Micheli (2018)
Liquid swine waste (LSW) has high pollutant potential to the soil and water. Among the chemical elements present in LSW there are heavy metals as copper (Cu2+) and zinc (Zn2+), which in high concentrations are toxic elements to plants and living beings in general. Effective management of liquid swine waste aiming to reduce environmental contamination can be achieved by means of sorbent material use. Natural materials, such as clay, have the ability to absorb metals from aqueous solutions. Natural materials, such as clay, have the ability to absorb metals from aqueous solutions. Metabasalt powder is waste that comes from mining, and due to its composition, it presents high sorption potential and use in these cases. Therefore, the goal of this work was to evaluate if metabasalt powder presents sorption capacity for copper (Cu2+) and zinc (Zn2+) ions. For that, seven doses of metabasalt powder were tested (0, 4, 10, 20, 40, 80 and 160 kg/m3 of LSW) in four contact times (9, 21, 42 and 84 days) between powder and waste, determining the concentration of these ions (copper and zinc) and the pH in the LSW total, solid and liquid fractions. Metabasalt powder was effective in the sorption of copper and zinc ions up to the dose of 10 kg/m 3at a contact time of 10 days, reducing the concentration of these ions in the liquid fraction. Doses above 10 kg /m 3occurred, however, the release of the ions in the most recalcitrant forms by metabasalt powder to the LSW. These results corroborate that metabasalt powder is effective as Cu2+ and Zn 2+ fixer in a determined dose and contact time, being an alternative of use as decontaminanting material, concentrating ions in the solid phase.